'BARI Masur‐9': An extra‐early lentil cultivar for a rice‐based cropping system in Bangladesh. Issue 3 (28th June 2022) - Shahin Uz Zaman, Md; Alam, Md Jahangir; Golam Azam, Md; Shahin Iqbal, Md; Ariful Islam, Md; Sarkar, Debashish; Aktar Uz Zaman, Md; Shamsul Alam, Md; Mahbubul Alam, A. K. M.; Altaf Hossain, Md; Ali, Md Omar; Sarker, Debasish; et al.
Abstract: Lentil ( Lens culinaris Medik) is the third‐most important grain legume in the world. In Bangladesh, it is important for human food and nutrition, animal feed, and sustainable rice‐based cropping systems. However, lentil area is declining due to competition with other winter and spring crops, particularly irrigated spring rice (boro rice; Oryza sativa L.). To increase lentil production, the extra‐early (<95 d) lentil line LRIL‐22‐70 was selected to grow in the short fallow period between monsoon and spring rice under a proposed new cropping pattern. LRIL‐22‐70 was identified from a recombinant inbred line population through rigorously evaluated in diverse agro‐ecological conditions of Bangladesh and released for commercial cultivation by Pulses Research Centre, BARI, as 'BARI Masur‐9' (Reg. no. CV‐36, PI 700307) in 2018. BARI Masur‐9 is a transgressive segregant for earliness (matures in <93 d) and fits well in the new monsoon rice–lentil–spring rice cropping pattern. It is a medium‐seeded (2.38 g 100 –1 seed) cultivar with high tolerance to Stemphylium blight. The average seed yield of BARI Masur‐9 was 1, 201 kg ha –1, with higher concentrations of Fe (73 mg kg −1 ) and Zn (61 mg kg −1 ) compared with other genotypes; thus, BARI Masur‐9 contributes to combatting micronutrient malnutrition in Bangladesh. BARI Masur‐9, the first extra‐early lentil cultivar, can successfully be grown to replace fallow between rice as a new cropping pattern monsoon rice–lentil (BARI Masur‐9)–spring rice in about 8 million ha in Bangladesh, eastern Indian states, and eastern Nepal. Core Ideas: BARI Masur‐9 is an extra‐early (85–90 d) lentil cultivar that fits in the monsoon rice–lentil–spring rice cropping pattern. BARI Masur‐9 seed is enriched with Fe (73 mg kg −1 ) and Zn (61 mg kg −1 ). BARI Masur‐9 is tolerant to Stemphylium blight and root rot diseases.